Occurrence of pathogenic bacteria and water quality of the surface water in the Kelani river basin, Sri Lanka - Mahagamage, M.G.Y.L.; Pathirage, M.V.S.C.; Manage, P.M. (Proceedings of the Twenty second Scientific Sessions of the Sri Lanka Association for Fisheries and Aquatic Resources, 20th May 2016. Auditorium o f National Aquatic Resources Research and Development Agency, Colombo 15, Sri Lanka., 2016)
Attached
Keywords: Kelani river basin; surface water; physico-chemical parameters; Shigella spp. Salmonella spp. and Campylobacter spp.